2009
DOI: 10.1038/ismej.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Life without light: microbial diversity and evidence of sulfur- and ammonium-based chemolithotrophy in Movile Cave

Abstract: Microbial diversity in Movile Cave (Romania) was studied using bacterial and archaeal 16S rRNA gene sequence and functional gene analyses, including ribulose-1,5-bisphosphate carboxylase/ oxygenase (RuBisCO), soxB (sulfate thioesterase/thiohydrolase) and amoA (ammonia monooxygenase). Sulfur oxidizers from both Gammaproteobacteria and Betaproteobacteria were detected in 16S rRNA, soxB and RuBisCO gene libraries. DNA-based stable-isotope probing analyses using 13 C-bicarbonate showed that Thiobacillus spp. were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(161 citation statements)
references
References 34 publications
6
152
1
2
Order By: Relevance
“…Avenues for understanding alternate non-photosynthetic primary production strategies are limited to subterranean or deep-sea ecosystems that function in the absence of sunlight. A significant amount of research has been devoted to characterizing primary production in ecosystems such as hydrothermal vents (reviewed by Nakagawa and Takai, 2008) and sulfidic caves (Sarbu et al, 1996;Chen et al, 2009;Engel et al, 2010;Jones et al, 2012), where supplies of reduced sulfur, hydrogen or methane support rich chemolithoautotophic activity; however, the energy dynamics of carbonate caves are less well defined. Carbonate cave communities are presumed to be sustained by allocthonous carbon sourced from photic surface ecosystems and entering the cave with vadose-zone drip water, surface water flow or the behavior of macrofauna (Laiz et al, 1999;Simon et al, 2003;Barton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Avenues for understanding alternate non-photosynthetic primary production strategies are limited to subterranean or deep-sea ecosystems that function in the absence of sunlight. A significant amount of research has been devoted to characterizing primary production in ecosystems such as hydrothermal vents (reviewed by Nakagawa and Takai, 2008) and sulfidic caves (Sarbu et al, 1996;Chen et al, 2009;Engel et al, 2010;Jones et al, 2012), where supplies of reduced sulfur, hydrogen or methane support rich chemolithoautotophic activity; however, the energy dynamics of carbonate caves are less well defined. Carbonate cave communities are presumed to be sustained by allocthonous carbon sourced from photic surface ecosystems and entering the cave with vadose-zone drip water, surface water flow or the behavior of macrofauna (Laiz et al, 1999;Simon et al, 2003;Barton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among the eight Crenarchaeota OTUs, three were grouped with soil archaea, one was related to the Nitrosocaldus genus, and four were archaea from a marine environ- ment. The Euryarchaeota and Creanarchaeota taxa are dominant in archaea communities in limestone caves (Chelius and Moore, 2004;Chen et al, 2009), including Crenarchaeota from marine environments that have previously been found in caves (Chelius and Moore, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…These micro-organisms are a monophyletic group of phenotypically diverse prokaryotes. Initially, it was believed that they were found only in extreme environments; however, several articles have demonstrated that archaea probably occur in all environments that support life, including caves (Gonzalez et al, 2006;Chen et al, 2009;Jarrel et al, 2011). This group was found to be important for ecological relationships in several environments, particularly because of their role in biogeochemical cycles (Kudo et al, 1997;Chen et al, 2009;Jarrel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…En contraste con los ambientes subaéreos dominados por comunidades fotosintéticas, los microbios subterráneos requieren un metabolismo quimiosintético para la productividad primaria, tal vez confinado a la oxidación de compuestos con azufre y hierro (principales fuentes de energía de tales ambientes) para sustentar su crecimiento y continuidad (Sarbu et al, 1996;Chen et al, 2009;Porter et al, 2009). Debido a que estas vías metabólicas son menos energéticas que la fotosíntesis (i.e.…”
Section: Los Ambientes Subterráneosunclassified